2023
DOI: 10.1017/s0305000923000557
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and fathers’ infant-directed speech have similar acoustic properties, but these are not associated with direct or indirect measures of word comprehension in 8-month-old infants

Audun ROSSLUND,
Silje HAGELUND,
Julien MAYOR
et al.

Abstract: Previous research on infant-directed speech (IDS) and its role in infants’ language development has largely focused on mothers, with fathers being investigated scarcely. Here we examine the acoustics of IDS as compared to adult-directed speech (ADS) in Norwegian mothers and fathers to 8-month-old infants, and whether these relate to direct (eye-tracking) and indirect (parental report) measures of infants’ word comprehension. Forty-five parent-infant dyads participated in the study. Parents (24 mothers, 21 fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 67 publications
6
5
1
Order By: Relevance
“…Finally, while gender-differences was not a primary focus of the current study, it is interesting that, irrespective of register, the fathers in our sample had overall more distinct consonant contrasts than mothers. This contradicts previous studies, albeit in other languages, that mostly report more contrastive VOT patterns in women than men (Li, 2013;Swartz, 1992;Whiteside & Irving, 1997), yet aligns with our results on vowels in IDS, which found that fathers had less variable and more distinctive vowel categories than mothers (Rosslund et al, 2023).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Finally, while gender-differences was not a primary focus of the current study, it is interesting that, irrespective of register, the fathers in our sample had overall more distinct consonant contrasts than mothers. This contradicts previous studies, albeit in other languages, that mostly report more contrastive VOT patterns in women than men (Li, 2013;Swartz, 1992;Whiteside & Irving, 1997), yet aligns with our results on vowels in IDS, which found that fathers had less variable and more distinctive vowel categories than mothers (Rosslund et al, 2023).…”
Section: Discussioncontrasting
confidence: 79%
“…Given the so-far sparsity of evidence, whether a relationship between parents' VOT and infants' language outcomes exists or not need to be corroborated by future research. However, as it stands, our study join others that found no correlation between features of parents' IDS and infants' language outcomes (Rosslund et al, 2023;Song et al, 2018;Suttora et al, 2017), and studies that challenge the overall 'clarity' view of IDS (Benders et al, 2019;Cox et al, 2023;Ludusan et al, 2021;Miyazawa et al, 2017). While we do not refute IDS as a register that is beneficial for language acquisition, either directly (for example via vowel space expansion; Kalashnikova & Burnham, 2018) or indirectly (for example via its attentional, emotional, and/or social properties; Golinkoff et al, 2015), our results suggest that, within the context of VOT of Norwegian stop consonants, IDS is not a more distinctive and didactic register as compared to ADS, and its realisation might instead be motivated by attentional and affective goals.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In line with previous above-reviewed research and meta-analytic evidence (where available), and per our detailed preregistration (https://osf.io/8k3eh), we expected that parents' IDS, compared to ADS, would be characterised by overall higher pitch, wider pitch range, slower articulation rate, longer vowel duration, increased vowel spaces, and more variable and less distinct vowel categories (Cox et al, 2022;Lovcevic et al, 2023;McMurray et al, 2013;Miyazawa et al, 2017;Rosslund et al, 2022Rosslund et al, , 2023. Crucially, we expected that the predicted IDS-ADS differences in pitch, articulation rate, vowel duration, vowel category variability, and vowel distinctiveness would decrease with infants' age, attributed to IDS becoming more similar to ADS (Bernstein Ratner, 1984;Cox et al, 2022;Rosslund et al, 2022Rosslund et al, , 2023. In contrast, we expected that the IDS-ADS differences in pitch range and vowel space areas would remain stable with infants' age (Cox et al, 2022).…”
Section: Introductionsupporting
confidence: 65%
“…(3) to support infants' linguistic development (Cristia, 2013;Ferjan Ramirez et al, 2020;Golinkoff et al, 2015;Snow & Ferguson, 1977). While these functions are not mutually exclusive, 2 it has been suggested that their relative importance shifts with infants' age: IDS as a tool to capture attention and convey emotional valence might be the main function in speech directed to young infants, while its facilitating role in language learning might emerge later in development (Fernald, 1992;Rosslund et al, 2023;Song et al, 2010;Spinelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%